Findings of Orchids in the basin of the Lower Sula (Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
The paper provides information on the whereabouts of four species of orchids (Epipactis helleborine, E. palustris, Listera ovata, Anacamptis palustris) in the basin of the lower Sula on the results of original research. It is characterized by ecological-coenotic features of the new locations of these species on the basis of the geobotanical descriptions of the communities. Epipactis helleborine was found in the array of mountainous deciduous forests, and Listera ovata in the floodplain forest on the bank of the river Rotten Orzhytsa (Grebenkovsky district, Poltava region) and eutrophic swamp in the outskirts of the village of Belousovk (Drabiv district, Cherkasy region). Meadow-wetland species – Anacamptis palustris and Epipactis palustris – form populations on the flood meadows in the vicinity of the village Mykhailivka of Cherkasy region, and the last type numerically found in specific habitats – willow-poplar neighborhoods of Sula. Mentioned localities of the species are represented by resocialise populations, mainly on right-bank of the river, which are confined to relevant ecological and nanotechnic conditions. Such spices as Epipactіs palustris and Anacamptis palustris are protected in the tract «Birch» on the territory of National Natural Park. Such spices as Epipactіs helleborine and Listera ovata are advisable to protect, consequently creating a Botanical Reserve and a Conservation Tract «Belousov».
Keywords: Epipactis helleborine, E. palustris, Listera ovata, Anacamptis palustris, Orchid species, rare species, location, security, basin of the lower Sula.